A model of hard X-rays emission from free expanding Plasma-Focus discharges - Fogliatto, Ezequiel Oscar; Gonzalez, Jose Hector; Barbaglia, Mario Oscar; Clausse, Alejandro (IOP Publishing, 2014)
Fil: Fogliatto, Ezequiel Oscar. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina